Mendorong Sektor Pendidikan di Perdesaan - Thomas Soseco (Universitas Negeri Malang, 2015)
Rural plays role as a supporting area for urban. Rural’s main activity is agriculture and natural resources explotation. In recent years, agricultural sector in rural area has been kicked out by other sectors.The implication is there is a shift in employment. This condition will influence income distribution in rural areas and then affects education sector. The research’s method is descriptive quantitative using secondary data provided by Indonesian Statistic Bureau (BPS). The change in rural’s economy pattern is proxied by population aged 15 years or over who work by main industry. Education’s quality is proxied by enrollment rate. The result of this research are: (1). There is positive relationship between the decreasing number of employment rate in agricultural sector and better income distribution in rural areas. (2). Better income distribution drives to higher enrollment rate. The recommendation is education sould be developed better in order to prevent employee to work in sectors other than agriculture.Keywords: rural, agriculture, education, enrollment rate